Analyzing Higher Order Thinking Skills (HOTS) in Arabic Language Instruction: Insights from Kitab Arabiyyah Baina Yadaik Volume 4A - Izzah, Hajryanti Syahrul; Fauji , Imam (Universitas Muhammadiyah Sidoarjo, 2024)
This study delves into the cognitive aspects of Higher Order Thinking Skills (HOTS) within the commands and instructions presented in Kitab Arabiyyah Baina Yadaik Volume 4A. Employing a qualitative library research method and content analysis, this investigation scrutinizes the instructional content of the book. Findings reveal that the book contains both HOTS-aligned instructions, encompassing skills such as analyzing, evaluating, and creating (C4, C5, C6), as well as non-HOTS instructions related to understanding and applying (C2, C3). The study underscores the importance of discerning and optimizing HOTS components in instructional materials, providing valuable insights for educators and curriculum developers in Arabic language education. Highlight: HOTS Identification: Examines HOTS and non-HOTS components in instructional content. Arabic Language Education: Focuses on enhancing Arabic language teaching and learning. Curriculum Optimization: Provides insights for educators and developers to improve curriculum materials. Keyword: Higher Order Thinking Skills (HOTS), Arabic Language Education, Instructional Content Analysis, Cognitive Skills, Curriculum Development